2015
DOI: 10.1016/j.ygyno.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional modeling of the human fallopian tube fimbriae

Abstract: Objective Ovarian cancer is the most lethal gynecological malignancy that affects women. Recent data suggests the disease may originate in the fallopian fimbriae; however, the anatomical origin of ovarian carcinogenesis remains unclear. This is largely driven by our lack of knowledge regarding the structure and function of normal fimbriae and the relative paucity of models that accurately recapitulate the in vivo fallopian tube. Therefore, a human three-dimensional (3D) culture system was developed to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…To capture the oncogenic drivers and tumor biology of HGSOC, fallopian tube‐based model systems may define the physiology and susceptibility of this epithelium to tumorous transformation. [ 214 ] So, much attention must be strictly paid to the human ovarian cancer cell models to explore different aspects in the tumorigenesis. In the future, as the avenues toward personalized precise medicine take a leap to explore more and more precise 3D cell models in vitro for patient‐specific therapies and wide patient‐derived cancer research, [ 144a ] immense efforts should be taken into account to explore growth conditions of particular subpopulations of tumor cells and high density coculture systems with immune cells or other cell subtypes.…”
Section: Conclusion and Outlook For Futurementioning
confidence: 99%
“…To capture the oncogenic drivers and tumor biology of HGSOC, fallopian tube‐based model systems may define the physiology and susceptibility of this epithelium to tumorous transformation. [ 214 ] So, much attention must be strictly paid to the human ovarian cancer cell models to explore different aspects in the tumorigenesis. In the future, as the avenues toward personalized precise medicine take a leap to explore more and more precise 3D cell models in vitro for patient‐specific therapies and wide patient‐derived cancer research, [ 144a ] immense efforts should be taken into account to explore growth conditions of particular subpopulations of tumor cells and high density coculture systems with immune cells or other cell subtypes.…”
Section: Conclusion and Outlook For Futurementioning
confidence: 99%
“…In the same way, a recent study by our group showed that 5 ng/ml of E2 could induce the mRNA expression of IL‐8 in BOEC and stimulate tumor necrosis factor and IL‐1B (pro‐inflammatory cytokines) expression after coculture with sperm (Yousef et al, ). Moreover, Eddie et al () reported that 2.7 ng/ml of E2 upregulated the transcription of IL‐8 in human oviductal epithelial cells. Collectively, oestradiol levels in the preovulatory FF are likely to induce an inflammatory response in the bovine oviduct.…”
Section: Discussionmentioning
confidence: 99%
“…Follicle maturation is autonomous Theca cells differentation is autonomous to the follicle Ovulation is autonomous to the follicle Physical rigidity alone can alter the hormone synthesis ratio (increasing rigidity favors androgen over estrogen) The ovulation rupture zone is a unique site Follicles reconstruct a holostructure after rupture in an autonomous manner The granulosa to luteal transition does not require exogenous cells Mouse follicles can function on a 28-day cycle First live birth in mouse from in vitro-grown 3D follicles First human MII eggs from in vitro-grown human follicles First ovarian bioprosthetic First microfluidic system that integrates ovarian function with reproductive tract tissues Zinc biology 20 billion zinc atoms are concentrated during meiotic maturation in the egg Telophase includes a zinc-depending zinc switch Zinc is exocytosed at the time of fertilization (zinc spark) Zinc is the cytoplasmic maturation factor Zinc is the factor responsible for the fast block to polyspermy Egg biology Meiotic chromosomes are ten times stiffer than mitotic chromosomes Meiotic chromosomes become more stiff with age Genes in polar body 1 and polar body 2 are indicative of egg maturity Terms coined Oncofertility -field of medicine at the intersection of cancer and reproductive care Bioprosthesis -tissue construct that restores soft organ function; originally ovarian bioprosthetic but term appropriate to any biologically constructed tissue Repropedia -short definitions, images or videos of reproductive terms; can be linked to any website Reprotopia -aggregate site for educational tools in the reproductive sciences EVATAR -name of microfluidic system connecting ovary, fallopian tube, uterus, cervix and liver tissue constructs; functions for 28 days Zinc spark -term for exocytotic release of zinc atoms at the time of fertilization Policies addressed Inclusion of sex as a biological variable in biomedical research Economic gaps for women in science Need for rational policies on the use of human gametes in research Insurance and reimbursment for oncofertility care Coordinated oncofertility science and medicine (a duet that recirculates) and a Quintet-MFP (Xiao et al 2017). In these systems, we cultured mouse ovarian follicles and ovaries along with human fallopian tubes, uterus, cervix and liver organoids (Laronda et al 2013, Eddie et al 2014, Arslan et al 2015, Eddie et al 2015, Zhu et al 2016, Olalekan et al 2017. This was a fascinating project and it took 5 years to invent a device that could support tissue-level function using fluidic channels that could manage the long-term (over 30 days), accurate movement of media between tissues.…”
Section: Follicle Biologymentioning
confidence: 99%